(untitled) (Baltic Journal of Real Estate Economics and Construction Management, 2013)
One of the main goals of the TÁMOP project called “Complex eco-environmental study of the cities in the Western Transdanubian region” was the study of the interaction between urban and natural areas. The major task was to reveal the conflicts and their location in the urban areas and use these data in the decision making process concerning the land use in the cities. The protection of the urban green areas and the prevention of the built structures had a top priority in this research considering the increase of the urban environmental life quality and the development of the environmental protection infrastructure. Therefore it was necessary to study and evaluate the so-called urban ecological parameters. The next step was the creation of an environmental cadastre and the elaboration of an eco friendly urban development plan proposal. The results of these complex studies should be part of the urban development processes in the future.